Antioxidant potentials of different potato genotypes (Bangladesh Journal of Agricultural Research, 2018)
The present investigation was undertaken to analyze the antioxidant potential of sixteen different potato genotypes. Eleven yellow fleshed potato genotypes namely Forza, Courage, Laura, Rosa Gold, Lady Rosetta, Cumbica, Asterix, Coronada, Granola, Cardinal and Diamant and five purple fleshed potato genotypes namely Jam Alu, KAC 10063, KAC 10064, KAC 10069, KAC 10097 were used as experimental materials. Total carotenoids, anthocyanin, phenolics, flavonoids, ascorbic acid and antioxidant activity in the above mentioned genotypes were determined to compare the antioxidant potentials of the genotypes. Analysis of above mentioned parameters resulted significant variation in their contents in both yellow and purple fleshed genotypes. The results indicate the purple fleshed genotypes showed significantly higher carotenoids, anthocyanin, flavonoids and total antioxidant activity than those of yellow fleshed genotypes. The findings also suggested the antioxidant activity of the genotypes positively correlates to the total content of carotenoids, anthocyanin and flavonoids. Since, purple fleshed genotypes showed higher antioxidant properties, the results of this study claim that the purple fleshed genotypes would be suitable for direct consumption as vegetables which might increase the health and food security of human beings.Bangladesh J. Agril. Res. 43(3): 369-381, June 2018